Adaptive Control Systems with Reference Models - Xusanov Suban Nurullayevich; Ibragimov Islomnur; Fayzullayev Sarvar Adham og‘li (Genius Journals, 2024)
The synthesis of adaptive control systems for continuous technological objects is a critical scientific problem with both theoretical and practical significance. This article focuses on formalizing the problem of synthesizing adaptive control for complex objects using reference models. The direct approach involves adjusting the system based on a predefined standard, minimizing discrepancies between the standard and the actual system. Additionally, the article explores methods for constructing regulators based on concepts from the theory of direct adaptive systems
Keywords: Adaptive control systems; Continuous technological objects; Reference models